Паровая бескислородная газификация в условиях полигенерации - Шевырёв С. А. Сергей Александрович; Стрижак П. А. Павел Александрович; Дитрих Р. -Ю. Ральф-Юве; Богомолов А. Р. Александр Романович (2021, 2021)
Заглавие с титульного листа